Factors associated with the coronally positioned flap of one or two teeth: a literature review - Vargas-del Campo, Miguel Fernando; Menestrey-Hoyos, Lissete (Revista Facultad de Odontología Universidad de Antioquia, 2015)
Introduction: marginal tissue recessions produce esthetic problems, tooth sensitivity, root caries, and difficulty to perform proper oral hygiene. There are various periodontal plastic surgery techniques for root coverage. The goal of this literature review is to assess factors associated with the coronally positioned flap technique to cover gingival recessions, bearing in mind that several variables can intervene in the complete coverage of root surface. Methods: this was a literature review on the coronally positioned flap technique for coverage of Miller class I and class II recessions of one or two teeth. It included articles published between 2000 and 2012 by searching the PubMed, Ebsco, and Cochrane databases for studies performed in humans, including longitudinal, transverse, and cohort studies, as well as clinical trials and meta-analyses. Results and conclusions: interdental papilla height, keratinized gingiva width, and gingival thickness are prognostic factors for total root coverage and its long-term stability. Integrity of the cemento-enamel junction is important in diagnosis and success of the technique; moreover, modification of root surface with technical and/or chemical mechanisms is a prerequisite. The coronally advanced flap technique combined with connective tissue, enamel matrix derivative, porcine collagen, or dermal matrix is effective in the treatment of Miller class I and class II gingival recessions, but the one with the greatest predictability is the bilaminar technique with connective tissue.